Figurative Language In Dr. Seuss The Lorax Movie Script: APragmatic Perspective - KURNIATI, DITA; , Dr. Maryadi, M.A; , Dra. Siti Zuhriah Ariatmi, M. Hum (2016)
This research is about figurative language. This research is descriptive qualitative research which aims at: (1) describing the types of figurative language, (2) clarifying the implicature, and (3) revealing violated maxim of Dr.Seuss The Lorax movie script. The data used in this research are utterances containing figurative language found in Dr.Seuss The Lorax movie. The techniques of collecting data used are documentation by content analysis and observation. The techniques of analyzing data are data reduction, data presentation and conclusion. One datum analysis answers three research problems at once. The data are analyzed by using figurative language theory of Perrine (1977), the speech situation is analyzed by using aspects of speech situation of Leech (1999), the implicature is analyzed by using the theory of Yule (1996), and the violated maxim is analyzed by using the theory of Grice (1975). From the analysis of 35 data number of figurative language, the result of the study shows that: (1) There are ten types of figurative language namely hyperbole (25.71%), metaphore (25.71%), personification (17.14%), simile (11.42%), metonymy (5.72%), irony (2.86%), understatement (2.86%), allusions (2.86%), idiom (2.86), and proverb (2.86%). (2) The implicature of figurative language covers conventioanl implicature (0%) and conversational implicature that consists of generalized conversational implicature (5.71%) and paticularized conversational implicature (94.29%). (3) The violated maxim of these data are violated maxim of quantity (14.28%), violated maxim of quality (74.30%), violated maxim of relevant (5.71%) and violated maxim of manner (5.71%). Keywords: descriptive qualitative, Dr.Seuss The Lorax, figurative language,implicature, violated maxim.